The Influence of Salary, Incentives and Work Discipline on The Perfomance of Employees in The Sales Division of PT. Mora Telematics Indonesia - Santoso, Faid Pratama Arif; Cahaya, Yohanes Ferry (Dinasti Publisher, 2025)
This study aims to determine the effect of salary, incentives, and work discipline on the performance of sales division employees at PT. Mora Telematika Indonesia, using quantitative methods with primary data through gform to respondents in the sales division at the company. The results are 1) Salary has a positive and significant effect on employee performance, namely 2.113>2.01290 with a significance value of 0.040<0.05. 2) Incentives have a positive and significant effect on employee performance, namely 2.976>2.01290 with a significance value of 0.000<0.05. 3) Work Discipline has a positive and significant effect on employee performance, namely 3.785>2.01290 with a significance value of 0.005<0.05. 4) Salary, Incentives, and Work Discipline simultaneously have a positive and significant effect on the performance of sales division employees at PT. Mora Telematika Indonesia, which is 61.961>3.20 and a significance value of 0.000<0.05. The conclusion of this study is that there is a positive and significant influence between Salary, Incentives, and Work Discipline on the Performance of Sales Division Employees at PT Mora Telematika Indonesia with a percentage of determination coefficient results of 78.4%.